2018
DOI: 10.1021/acssuschemeng.8b05334
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Extraction of Yttrium(III) Using 2-Ethylhexyl Phosphonic Acid Mono-2-ethylhexyl (EHEHPA) in a Microreactor: A Comparative Study

Abstract: Experiments were carried out in a slug flow microreactor to systematically investigate reaction behavior under variation of flow rate, and a comparative study was made. Y-junction microreactor and T-junction microreactor have been used to extract yttrium(III) using 2-ethylhexyl phosphonic acid mono-2-ethylhexyl (EHEHPA or P507). Results show that the maximum extraction efficiency of 90.4% in both microreactors could be achieved corresponding to the minimum flow rate of 10 and 100 μL/min. The values of specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In this study, the mixture of isobutane and 1-butene was the dispersed phase, whereas sulfuric acid was the continuous phase. The flow pattern of heterogeneous systems in microchannels is mainly laminar flow or slug flow. , However, droplet flow was observed in this study. There is a big difference between the physical properties of the hydrocarbon phase and the H 2 SO 4 phase.…”
Section: Results and Discussionmentioning
confidence: 58%
“…In this study, the mixture of isobutane and 1-butene was the dispersed phase, whereas sulfuric acid was the continuous phase. The flow pattern of heterogeneous systems in microchannels is mainly laminar flow or slug flow. , However, droplet flow was observed in this study. There is a big difference between the physical properties of the hydrocarbon phase and the H 2 SO 4 phase.…”
Section: Results and Discussionmentioning
confidence: 58%
“…In addition, publications within our research group also studied the intensified extraction and separation performance of the related rare earths in the microreactor and compared the liquid–liquid extraction of rare earth elements in a Y-junction serpentine microreactor, T-junction microreactor, and conventional extractor. The interaction of rare earth elements with P507 in a microfluidic extraction system containing lactic acid as the complexing agent was characterized by spectroscopic analysis (FT-IR analysis, UV–vis analysis, NMR analysis, MS analysis), which demonstrated that the extracted complexes located in the center are formed by cation exchange and the coordination process between PO and RE 3+ . The literatures proves that the application of microchemical technology in the rare earth separation and extraction industry is environment friendly with broad prospects. Microfluidic technology can effectively solve the common problems in the conventional solvent extraction process as a new low-cost technology.…”
Section: Current Implementation Of Microreactors In Extraction and Se...mentioning
confidence: 98%
“…Likewise, they raise the possibility of accessing the ultimate product with high purity. However, besides these favorable characteristics, a need for more severe stripping conditions, along with environmental pollutions resultant from harmful P or S elements in the chemical compounds of these extractants, are among the disadvantages of this extractant [35]. In addition, the structure of the extractant and the type of atom-donor electrons play signi cant roles in making decisions about the separation behavior of metal ions [36].…”
Section: Introductionmentioning
confidence: 99%